2005
DOI: 10.1161/circulationaha.105.552984
|View full text |Cite|
|
Sign up to set email alerts
|

Anticoagulation Therapy in Atrial Fibrillation in Combination With Acute Myocardial Infarction Influences Long-Term Outcome

Abstract: for the RIKS-HIA Registry Background-The American and European guidelines do not agree with regard to antithrombotic treatment in patients with atrial fibrillation (AF) and acute myocardial infarction (AMI), thus causing uncertainty among physicians. We investigated the prescription of oral anticoagulation (OAC) in patients discharged alive with AF after an AMI and the influence of OAC treatment on 1-year mortality. Methods and Results-This was a prospective cohort study using data from the Register of Informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 80 publications
(32 citation statements)
references
References 32 publications
1
30
0
Order By: Relevance
“…Of these, 14 studies [50][51][52][53][54][55][56][57][58][59][60][61][62][63] (in 14 articles) reported data from observational designs, both prospective [50][51][52][53][54][55] and retrospective [56][57][58][59][60][61][62][63] in nature. The remaining four studies in 10 articles [64][65][66][67][68][69][70][71][72][73] were originally designed to assess the effectiveness of an anticoagulant without additional APT.…”
Section: -73mentioning
confidence: 99%
See 4 more Smart Citations
“…Of these, 14 studies [50][51][52][53][54][55][56][57][58][59][60][61][62][63] (in 14 articles) reported data from observational designs, both prospective [50][51][52][53][54][55] and retrospective [56][57][58][59][60][61][62][63] in nature. The remaining four studies in 10 articles [64][65][66][67][68][69][70][71][72][73] were originally designed to assess the effectiveness of an anticoagulant without additional APT.…”
Section: -73mentioning
confidence: 99%
“…Retrospective outcomes (n = 8) [56][57][58][59][60][61][62][63] Prospective outcomes (n = 6) [50][51][52][53][54][55] Of the studies reporting non-randomised comparisons, six were retrospective, [56][57][58][60][61][62][63] and the time of APT use varied between the studies. The majority of these studies consisted of a retrospective review of medical records where prior knowledge of allocation of therapy was not possible.…”
Section: Ffaacs 41mentioning
confidence: 99%
See 3 more Smart Citations